Assessment of Synchronous Generator’s Influence on Transmission Network with Significant Level of Voltage Unbalance - Sarnet, T.; Kilter, J. (Elektronika ir Elektrotechnika, 2012)
The electrified railway systems are known as source of large voltage unbalances in the transmission network. The electrified railway connection load flow analysis provides good overview of voltage unbalance distribution over transmission network. The level of unbalance is expressed by voltage unbalance factor, which value depends on network load conditions, network strength and selected traction system solution. In this paper a fragment of Estonian transmission network is modelled in PSCAD together with perspective electrified railway system and CHP plant in order to analyse the network operation in different conditions and determine the impact of synchronous generator to distribution of voltage unbalance. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2796